PRACTICE-BASED LEARNING PROCESS AS A SOLUTION TO IMPROVE THE EDUCATION QUALITY OF ELEMENTARY SCHOOL STUDENTS IN SUPPORTING THE REALIZATION OF THE 2030 SDGs (Study Case at SD Negeri 1 Dajan Peken) - Diana, Shelly; Purnami, Ni Made Rina (Universitas Islam Indonesia, 2021)
Sustainable Development Goals (SDGs) is the country's framework for the next 15 years, which contains a set of agreed transformative goals that apply to all nations. The SDGs contain 17 main goals, one of the goals is related to realizing inclusive and quality education. The education process will form quality individuals and play a major role in the process of advancing a country (Binus, 2020). However, the Indonesian education system still has various problems, such as the application of theoretical learning that can't be accompanied by a practical process, so that students, especially elementary school students, lose interest in learning. According to UNESCO data, the reading interest of the Indonesian people is even worth 0.001%, which means that out of 1,000 Indonesians, only one person is diligent in reading. Theoretical learning accompanied by a lack of student's interest in reading will cause the learning process to be less effective and the quality of Indonesian education will decline. This would be an obstacle to realizing the SDGs goals in education. To overcome these problems, the authors propose the application of Practice-Based Learning Process as a Solution to Improve the Education Quality of Elementary School Students in Supporting the Realization of 2030 SDGs. In examining these problems, the authors researched at the State Elementary School 1 Dajan Peken, Bali. The purpose of this study was to determine the learning development of elementary school children in Bali after the pandemic and provide solutions to increase student interest in learning through a practice-based learning process. A research method is a qualitative approach through observation and interviews. The results showed that most of the students did not like theoretical learning and wanted practical learning. With this research, researchers hoped that it can be a reference for readers and stakeholders to increase students' interest in learning. Keyword: Education, Practice Based Learning, SDGs